Pengaruh Budaya Organisasi dan Sikap Kerja Terhadap Kinerja Karyawan Di Dinas Kebudayaan dan Pariwisata Kota Bandung - Nuraini Wulandari; Bachruddin Saleh Luturlean (RELASI : JURNAL EKONOMI, 2023)
The background in this research is that there are problems with organizational culture and work attitudes that are being faced by Dinas Kebudayaan and Pariwisata Kota Bandung. Therefore, the purpose of this study was to examine the effect of organizational culture and work attitudes on employee performance. Researchers want to know and overcome the problems that are happening to the object being addressed. The method used is a quantitative method with descriptive and causal techniques. Sampling used a non probability random sampling method, with a saturated sample of 68 employees. The results of the analysis using software SPSS 21 which proves that organizational culture and work attitudes have a positive and significant effect simultaneously and partially on the performance of the intended object. Partial influence of organizational culture is 23.6% and work attitude is 13.8%. Meanwhile, simultaneously at 37.4%. The conclusion of this study is organizational culture, work attitudes, and employee performance as seen from the results of the overall description analysis included in the good category. This shows that the higher the organizational culture and employee work attitudes, the higher the employee performance at the Dinas Kebudayaan dan Pariwisata Kota Bandung.